MiR‐129‐5p inhibits proliferation, migration, and invasion in rectal adenocarcinoma cells through targeting E2F7. Issue 7 (13th February 2020) - Wan, Ping; Bai, Xuan; Yang, Chao; He, Tian; Luo, Lilin; Wang, Yun; Fan, Minmin; Wang, Zhilin; Lu, Liming; Yin, Yajing; Li, Sisi; Guo, Qiang; et al.
Abstract: microRNAs (miRNAs), a kind of small noncoding RNAs, are considered able to regulate expression of genes and mediate RNA silencing. miR‐129‐5p was shown to be a cancer‐related miRNA. However, the influence of miR‐129‐5p in rectal adenocarcinoma (READ) development remains to be determined. Based on the TCGA data, downregulation of miR‐129‐5p in READ samples was observed. Manual restoration of the miR‐129‐5p in SW1463 and SW480 cell lines significantly inhibited invasion, migration, and proliferation of READ cell lines, while the apoptosis ability was enhanced. Meanwhile, we found E2F7 acted as a potential target of miR‐129‐5p and was upregulated in READ samples. E2F7 upregulation reversed the repression of miR‐129‐5p on READ development. Finally, in vivo experiments showed that inhibition of tumor growth in nude mice was achieved through upregulating miR‐129‐5p. Overall, our findings suggest increasing of miR‐129‐5p leads to the suppression of READ progression through regulating the expression of E2F7, which may provide novel insights into the treatment of READ. Abstract : In summary, our study proved that miR‐129‐5p might restrain proliferation, migration, and invasion of rectal adenocarcinoma (READ) cells, while promoting apoptosis of cells, and in vivo inhibit READ tumor growth through targeting E2F7. Hopefully, our study could contribute to the understanding of READ, and shed light on READ diagnosis and treatment.